PELAPORAN PAJAK PENGHASILAN PELAKU USAHA MIKRO KECIL DAN MENENGAH CV. KIJANG MAS’69 - Eva Faridah; Elis badriah; Asep Nurwanda (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
In order to make it easier to do tax calculations and self-assessment reporting, the Micro, Small and Medium Enterprises CV. Kijang Mas'69 needs to prepare fiscal reporting. The preparation of fiscal reporting is based on commercial financial reporting that is adjusted to tax regulations. For Micro, Small and Medium Enterprises, CV. Kijang Mas '69 can use the basis of the Financial Accounting Standards Untitas Without Public Accountability (SAK-ETAP) which has been made by the Indonesian Institute of Accountants. CV. Kijang Mas '69 does not yet have an understanding of taxes, especially not understand the calculation of taxes to be paid and do not understand the making of tax reporting. Based on the problems faced by Micro, Small and Medium Enterprises, CV. Kijang Mas '69, therefore there is a need for Reporting Training to provide solutions to the problems found. Among other things, providing training in the preparation of simple financial reports to help with these problems, with the implementation of this service activity, it can increase awareness to carry out their obligations in paying taxes. Keywords: Tax Reporting, Income Tax, UMKM